2003
DOI: 10.1188/03.onf.65-73
|View full text |Cite
|
Sign up to set email alerts
|

The PRO-SELF©: Pain Control Program—An Effective Approach for Cancer Pain Management

Abstract: Adequate pain relief is vital to decreasing cancer morbidity and improving patients' quality of life. The PRO-SELF: Pain Control Program should be implemented in all settings where cancer care takes place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…A key finding from studies in this field is that education for self-management of cancer pain should be integrated into routine practice [29,19,30]. Despite optimism that this can be achieved 'without undue extra resources or time' [14, p393] there are numerous factors, often presented as barriers, which influence the implementation of patient education for selfmanagement -including health professionals' knowledge, attitudes and beliefs [26,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key finding from studies in this field is that education for self-management of cancer pain should be integrated into routine practice [29,19,30]. Despite optimism that this can be achieved 'without undue extra resources or time' [14, p393] there are numerous factors, often presented as barriers, which influence the implementation of patient education for selfmanagement -including health professionals' knowledge, attitudes and beliefs [26,30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown that 'self-action strategies' to manage the effects of advanced cancer on appetite and eating can lead to changes in patients' thinking and behaviour which enhance well-being [17]; the importance of recognizing and supporting patients' selfmanagement strategies in regard to medicines taking when their life expectancy is reduced by advanced cancer has been demonstrated; and, importantly, self-management has been shown to fluctuate during the trajectory of an illness, with advancing metastatic disease and/or feeling more ill prompting changes in how actively individuals self-manage [19]. Supporting self-management has become a standard approach for health care professionals working with people who experience chronic non-cancer pain [21,22] and many studies and reviews have reported that patient-focused educational interventions, including self-management, can also improve pain control in patients with advanced cancer [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This descriptive correlational study is part of a large randomized clinical trial (RCT) that evaluated the effectiveness of the PRO-SELF© Pain Control Program compared to standard care in improving cancer pain management (12)(13)(14). Two hundred and twelve oncology outpatients were recruited from seven outpatient settings in Northern California including a university-based cancer center, two community-based oncology practices, one outpatient radiation therapy center, one health maintenance organization, one Veterans Administration facility, and one military hospital.…”
Section: Sample and Settingsmentioning
confidence: 99%
“…Side effects of analgesic medications were evaluated on a weekly basis using the checklist shown in Figure 1. Intensity of side effects was rated using a 0 to 4 scale (i.e., 0 = did not have, 1 = slight, 2 = moderate, 3 = severe, and 4 = very severe) (14). Side effect data from the end of the first week of the RCT are reported in this paper.…”
Section: Instrumentsmentioning
confidence: 99%
“…Family caregivers participated when available. A detailed description of the PRO-SELF ß intervention has been published previously (West et al, 2003). Briefly, the intervention lasted for 6 weeks and consisted of three home visits (weeks 1, 3, and 6) and three telephone calls (weeks 2, 4, and 5).…”
Section: Evolution Of the Qualitative Component Of The Pro-self ß Paimentioning
confidence: 99%